Peran Orangtua Terhadap Motivasi Anak dalam Belajar Al-Quran di Taman Kanak-Kanak - Nurianna Nurianna; Nurhafizah Nurhafizah (SELING: Jurnal Program Studi PGRA, 2020)
The purpose of this study was to determine the relationship of the role of parents to children's motivation to learn the Koran in Jamik Al-amin Lubuk Buaya Kindergarten. This type of research is correlation by applying quantitative methods. The population of this research is all parents in the children's park jamik al-amin lubuk crocodile. Samples taken using the method of total sampling or saturated sample that is all parents of children used as samples. Starting from the parents of group B1 children are 20 people and B2 groups are 10 people. So the number of samples is 30 parents of children. The data collection method is a questionnaire and data collection tool is a list of written statements. The data analysis technique was used with the product moment formula which was assisted by the SPSS version 16.0 application. Obtained results of researchers coefficient determination of the relationship of the role of parents to the motivation of children learning the Koran by 0.0025%. The correlation coefficient between the role of parents on children's motivation to learn the Koran is 0.049. This means that the role of parents by 0.49% on children's motivation to learn the Koran is significant at the level of 5%. It can be concluded that the role of parents has a close relationship or contribution to children's motivation to learn the Koran in the Jamik Al-amin Lubuk Buaya Kindergarten by 0.49%.